Correlation between ankle muscle strenght and the disturbs in foot posture - Silva, Ana Flávia Spadaccini; Oliveira, Rodrigo Franco; Silva, Joyce Karla Machado da; Júnior, Rinaldo Bernardelli; Menossi, Berlis Ribeiro dos Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The ankle and foot are responsible for the support base of the whole body and variations in the foot posture influences the function of lower limbs. Objective: To observe whether there is a relationship between the isokinetic peak torque of ankle muscles with different types of foot. Method: The sample consisted of 32 volunteers, divided intentionally into 3 groups (normal, flat and cavus) according to the classification of the type of foot. They were evaluated in an isokinetic dynamometer Biodex 4 Medical Systems, for analysis of ankle muscles peak torque in flexion and dorsal plantar, inversion and eversion in concentric contraction at 30 and 60°/s speeds. Results: There was positive moderate correlation between cavus group and the inversion peak torque in the dominant lower limb and negative moderate correlation on the not dominant lower limb. The flat foot group presented correlation with peak torque in the plantar flexion movement at a speed of 30°/s in non-dominant leg, which was negative moderate correlation. The normal foot group was correlated with peak torque of dorsiflexion movement in the dominant lower limb on 60 °/s speed and the non-dominant leg on 30°/s, been negative moderate correlations. Conclusion: The foot types were correlated with the ankle muscles, showing that alterations on the position of the feet, the ankle muscle strength changes depending on it.